2014
DOI: 10.3144/expresspolymlett.2014.2
|View full text |Cite
|
Sign up to set email alerts
|

Interactions, structure and properties in poly(lactic acid)/thermoplastic polymer blends

Abstract: Abstract. Blends were prepared from poly(lactic acid) (PLA) and three thermoplastics, polystyrene (PS), polycarbonate (PC) and poly(methyl methacrylate) (PMMA). Rheological and mechanical properties, structure and component interactions were determined by various methods. The results showed that the structure and properties of the blends cover a relatively wide range. All three blends have heterogeneous structure, but the size of the dispersed particles differs by an order of magnitude indicating dissimilar in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
71
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 75 publications
8
71
1
2
Order By: Relevance
“…The large size of TPS granules showed that untreated TPS had failed to improve the interfacial interaction between the hydrophobic PLA and the hydrophilic TPS, thus producing immiscible blends of PLA/TPS blends. Imre et al (2014) reported that a heterogeneous structure from immiscible blends could weaken the interaction between the blends in the system. Thus, a large phase separation could be seen in the SEM micrograph.…”
Section: Blend Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…The large size of TPS granules showed that untreated TPS had failed to improve the interfacial interaction between the hydrophobic PLA and the hydrophilic TPS, thus producing immiscible blends of PLA/TPS blends. Imre et al (2014) reported that a heterogeneous structure from immiscible blends could weaken the interaction between the blends in the system. Thus, a large phase separation could be seen in the SEM micrograph.…”
Section: Blend Morphologymentioning
confidence: 99%
“…It also had good stiffness and strength (Imre et al 2014). However, PLA has some drawbacks, such as brittleness, moisture problems, and, most importantly, it is produced at a relatively high price (Acton 2013;Imre et al 2014). To reduce these undesirable properties of PLA, researchers have attempted to modify the PLA in many ways, such as by plasticization, copolymerization, blending, and composite production, to enhance its properties and, most importantly, to lower the cost of producing the PLA itself (Auras et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most influential factors, during the formation of the microstructure, are the compositional ratio, the viscosity and the interfacial bond between the phases [10]. By combining the effects of these factors, different complex morphological structures can be formed, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In case of preparing polymer blends, the final morphology strongly depends on droplet breakup and coalescence processes during shear flow [7]. These two forces both dominate under transient condition, and their balance in steady state was described by Taylor's theory of Capillary number [8,9].…”
Section: Introductionmentioning
confidence: 99%